Analysis of defect mechanisms in nonstoichiometric ceria–zirconia by the microwave cavity perturbation method. Issue 5 (31st December 2022) - Steiner, Carsten; Hagen, Gunter; Kogut, Iurii; Fritze, Holger; Moos, Ralf
Abstract: In this microwave study, the defect chemistry of ceria–zirconia solid solutions (CZO, Ce1− y Zr y O2− δ ) was investigated at high temperatures by a resonant microwave method. Specifically, the effects of temperature and Zr content on the dielectric properties and defect chemistry mechanisms in CZO were analyzed. Experiments were performed on a series of different CZO powders ( y = 0.2, 0.33, 0.50, 0.67). Measurements at 600°C and different oxygen partial pressures ( p O2 = 10 −26 –0.2 bar) confirm a dominant n ‐type conduction of small‐polarons in CZO due to the preferred formation of oxygen vacancies, which is also supported by a multimodal analysis. Polarization losses were found to be negligible in the GHz range. Furthermore, an increased relative permittivity was observed in CZO, which correlates with the concentration of oxygen vacancies in CZO. Our microwave study is the first to provide a comprehensive data set for the dielectric properties of CZO powder sample in a wide range of different conditions. In addition, the connection of dielectric properties to CZO defect chemistry mechanisms is presented. The results are in good agreement with findings in the literature and may contribute to a better understanding of microwave‐based state diagnosis of CZO‐based materials, as it discussed for three‐way catalysts.